ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI (Studi Kasus pada RS Umum Daerah dr. H. Moh. Anwar) - Moh Farizan Thoriq; Dwiyani Sudaryanti; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study was to analyze and examine the effect of user involvement in the development of accounting information systems, personal technical skills of accounting information systems, top management support, and user training and education programs on the performance of accounting information systems. This study uses a quantitative approach. The location of this research was conducted at the Regional General Hospital Dr. H. Moh. Anwar, Sumenep Regency. This research will be conducted in November 2022 until it is completed. The population in this study were all employees/staff of the Dr. Regional General Hospital. H. Moh. Anwar, Sumenep Regency, finance/accounting department. Sampling was done based on the purposive sampling method, with predetermined criteria, in order to obtain 50 samples. The results of the study state that partially user involvement in the development process, personal technical ability, top management support and user training & education have a significant effect on the performance of accounting information systems at the Regional General Hospital dr. H. Moh. Anwar.Keywords: User involvement in the development of accounting information systems, personal technical skills of accounting information systems, top management support, as well as user training and education programs and accounting information system performance